Association Between Urine Output and Mortality in Critically Ill Patients: A Machine Learning Approach. Issue 3 (March 2022) - Heffernan, Aaron J.; Judge, Stephanie; Petrie, Stephen M.; Godahewa, Rakshitha; Bergmeir, Christoph; Pilcher, David; Nanayakkara, Shane
Abstract : OBJECTIVES: Current definitions of acute kidney injury use a urine output threshold of less than 0.5 mL/kg/hr, which have not been validated in the modern era. We aimed to determine the prognostic importance of urine output within the first 24 hours of admission to the ICU and to evaluate for variance between different admission diagnoses. DESIGN: Retrospective cohort study. SETTING: One-hundred eighty-three ICUs throughout Australia and New Zealand from 2006 to 2016. PATIENTS: Patients greater than or equal to 16 years old who were admitted with curative intent who did not regularly receive dialysis. ICU readmissions during the same hospital admission and patients transferred from an external ICU were excluded. MEASUREMENTS AND MAIN RESULTS: One hundred and sixty-one thousand nine hundred forty patients were included with a mean urine output of 1.05 mL/kg/hr and an overall in-hospital mortality of 7.8%. A urine output less than 0.47 mL/kg/hr was associated with increased unadjusted in-hospital mortality, which varied with admission diagnosis. A machine learning model (extreme gradient boosting) was trained to predict in-hospital mortality and examine interactions between urine output and survival. Low urine output was most strongly associated with mortality in postoperative cardiovascular patients, nonoperative gastrointestinal admissions, nonoperative renal/genitourinary admissions, and patients with sepsis. CONCLUSIONS: Consistent with current definitions of acute kidney injury, a urine output threshold of less than 0.5 mL/kg/hr is modestly predictive of mortality in patients admitted to the ICU. The relative importance of urine output for predicting survival varies with admission diagnosis.